Construction of Cultural Resilience through the Exploration of Seblang Olehsari Banyuwangi Ritual Philosophical Value - Asha, Asha; Mabruri, Kholid; Komariah, Nurul; Imron, Ali (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
Seblang Olehsari Banyuwangi is a sacred ritual containing moral messages symbolized in symbols. The symbols need to be explored in order to be understood better and serve as a guideline for the community to implement collective norms as an effort to strengthen social solidarity. Strong social solidarity will strengthen cultural resilience to cope with the current globalization of culture. Recognizing that to construct social solidarity requires a comprehensive understanding of the philosophical aspects, so that Seblang ritual from the philosophical aspect needs to be studied more deeply. Therefore, this research aimed to explore the philosophical value of Seblang Olehsari ritual as cutural resilience. The benefits that can be taken, this research was expected to show to the society about the need to maintain Seblang Olehsari ritual as one form of efforts to maintain the local wisdom. The type of this research was descriptive with in-depth interview data collection technique and participant observation. The data analysis process used philosophical approach, then examined the validity of data with data triangulation. The results of this research could be concluded that the philosophical values of Seblang ritual could be categorized based on ritual property and ritual procession that has the value of recommendation appreciate the universe and maintain the balance of the environment and preserve the nature. The construction of cultural resilience of philosophical value was shaped by cultural value systems, changing adaptation, integration functions and social cohesion and transformative.